Hubungan Frekuensi Konsumsi Jajanan Kemasan dan Minuman Manis terhadap Status Gizi Siswa Sekolah Dasar - Nur Diyanti, Prisma; Ruhana, Amalia (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Background: Nutritional problems in elementary school-aged children are still high in Indonesia, mostly caused by unhealthy eating patterns, such as consuming packaged sweet drinks. Objective: To analyze the relationship between the frequency of consumption of packaged sweet drinks and the nutritional status of grade 5 and 6 students at SDN Jagir Surabaya. Method: The research used a cross-sectional design with a sample of 40 students selected using proportional random sampling. Data were collected through FFQ interviews and BMI/U measurements. Results: There was no significant relationship between consumption of packaged snacks and nutritional status (p > 0.05), but there was a significant relationship between consumption of packaged sweet drinks and nutritional status (p = 0.014, r = 0.373). Conclusion: Excessive consumption of packaged sugary drinks can affect students' nutritional status, especially increasing the risk of obesity. Implications: It is important to educate students and parents about healthy eating patterns.